Postavljanje ciljev v delovni terapiji in uporaba Kanadske metode za ocenjevanje izvajanja dejavnosti - Šuc, Lea (Rehabilitacija (Ljubljana), 2018)
Background: It has been recognized that the Canadian Occupational Performance Measure (COPM) is a useful tool for setting goals in therapy. Since this is a semi-structured interview, the therapist's experience, skills and abilities, as well as knowledge of occupational therapy theory and practice, influence its outcomes. The aim of our study was to explore how goal setting is experienced by occupational therapists working at the University Rehabilitation Institute in Ljubljana. The research questions driving the study were: What are the experiences of novice and expert therapists with goal setting? How do therapists experience COPM? Methods: Eight occupational therapists participated in the study; four of them were novice therapists and four were considered experienced therapists. Data were gathered using in-depth interviews. Six therapists were also observed whilst conducting COPM. Thematic analysis was used to analyse the material. Findings: Five main themes emerged from the analysis: experience, familiarity with theory, differences between therapists, patient's wishes and the psychology of goal setting. In the participants' opinion, work experience importantly contributed to the following areas: communication, guidance, looking for solutions, flexibility, comparing with previous cases. Differences between novice therapists and experts could most often be observed in these areas. Conclusions: Therapists employed at the University Rehabilitation Institute in Ljubljana identified several factors they deemed important for setting goals and using COPM. They emphasized the significance of proper question formulation and interpretation of results as well as the ability to guide patients toward realistic goals. This information should be considered when planning additional courses, especially for less experienced therapists who might require more feedback on how to use COPM.
Keywords: Canadian Occupational Performance Measure; cilji; COPM; delovna terapija; Goals; Kanadska metoda za ocenjevanje izvajanja dejavnosti; occupational therapy; Rehabilitation